2008
DOI: 10.1097/01.phh.0000333879.55572.a4
|View full text |Cite
|
Sign up to set email alerts
|

Completeness of Reporting of Rabies Postexposure Prophylaxis in King County, Washington

Abstract: The completeness of rabies postexposure prophylaxis (PEP) reporting was evaluated in King County, Washington State. Information on rabies immune globulin prescriptions was obtained from hospital pharmacies associated with emergency departments in King County from 2003 to June 2006. Rabies immune globulin is given at the initiation of rabies PEP which is usually started at emergency departments. Because pharmacies are not regular sources of rabies PEP reporting, we compared pharmacy cases with cases reported vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…This may relate to differences in perceptions of rabies risk in areas that have low to negligible rates of terrestrial rabies. 16,18 However, any mammal is capable of acquiring and transmitting rabies; therefore, it is important for public health advocates to continue educational outreach efforts regarding the risk of rabies from contact with wildlife, regardless of the species of animal involved in the exposure. Appropriate risk assessment and judicious application of postexposure prophylaxis remain important focuses of rabies education for health-care providers in the United States.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may relate to differences in perceptions of rabies risk in areas that have low to negligible rates of terrestrial rabies. 16,18 However, any mammal is capable of acquiring and transmitting rabies; therefore, it is important for public health advocates to continue educational outreach efforts regarding the risk of rabies from contact with wildlife, regardless of the species of animal involved in the exposure. Appropriate risk assessment and judicious application of postexposure prophylaxis remain important focuses of rabies education for health-care providers in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Samples from 4 human patients suspected to have rabies were tested with a quantitative reverse transcription PCR assay, but results were negative for all 4. The province of Saskatchewan had the largest number of cases (n = 20), followed by Ontario (18) and Manitoba (15). Bats accounted for the highest proportion of cases (46 [49%]), followed by striped skunks (22 [24%]) and Arctic foxes (10 [11%]).…”
Section: Rabies In Canada and Mexicomentioning
confidence: 99%
“…4 Furthermore, for an SHD trying to develop reporting guidelines, input from local health department representatives during the formative stages of the system will promote the acceptability of surveillance and completeness of reporting. 13 Regardless of a jurisdiction's decision to invest in animal bite or PEP reporting, educational campaigns aimed at reducing rabies virus exposures and promoting correct use of PEP should be implemented. 6 …”
Section: • Conclusion and Recommendationsmentioning
confidence: 99%
“…14 However, a study in King County, Washington, found that 71 of 189 (37.6%) instances of PEP administration were not reported from 2003 to 2006. 15 In Illinois, 578 of 664 (87.0%) people reported with a potential rabies exposure in 2015 received at least 1 dose of PEP in an emergency department (ED) setting (Illinois Department of Public Health, unpublished data, 2015). The Cook County Department of Public Health operates an ED syndromic surveillance system that receives near-real-time data from all 20 acute care hospitals in the jurisdiction and 25 acute care hospitals in the surrounding area.…”
mentioning
confidence: 99%